Victory in Jeffery EugenidesThe Virgin Suicides Novel (1993): A Psychoanalytic Approach - Ikhsan, Yudi Muhammad, Dra. Phil Dewi Candraningrum, M. Ed, Siti Fatimah, S.Pd. M.Hum (2016)
The major problem in this study is how the major character proves his freedom, victory of life and depression in The Virgin Suicides novel by Jeffrey Eugenides. This study focuses on the one of the major characters namely Lux Lisbon (second younger sister), using the meaning of psychoanalytic analysis. The object of this study is Jeffrey Eugenides The Virgin Suicides novel published in 1993 by Harper Collins Canada. The type of this study is descriptive qualitative. The primary data source is the The Virgin Suicides itself and the secondary data sources are books or any information related to the practice of victory, depression the moral problem that support the psychoanalytic approach by Sigmund Freud. The technique of analyzing data in this research paper is descriptive. The researcher concludes that freedom, useless victory and depression is the individual emotions, it drives from system of personality. The psychological analysis shows that person's switched their identities coming from his id and fictional ego has pushed his to do some efforts to attain the superego and he must sacrifice everything. Finally, the psychological analysis shows that the human factor will exchange their characters because the activating personality aspects within the characters and the cause are among other family and environmental factors. Jeffrey Eugenides gives the important points when the major character, Lux Lisbon, gets the conflict between her id and superego to prove her freedom and victory for herself. The outcome of the study shows that the problem faced by the major character lux Lisbon causes the conflict of her mental condition. It comes because he struggles to get her victory and the depression for her life. Finally, she make a final choice to suicide herself because her depression of life and get victory for her life , but that is not real victory for us, it is a useless victory.